Evaluating the Dental Hygienists' Exposure to the Risk of Musculoskeletal Disorders - Ćwirzeń, Waldemar; Wagner, Leopold (European Journal of Dentistry, 2022)
Objectives The aim of the study was to evaluate dental hygienists' exposure to the risk of musculoskeletal disorders (MSDs), by the worksheets compatible with the Rapid Entire Body Assessment (REBA).Materials and Methods The research included 272 dental hygienists aged 23 to 52 years from the two administrative regions of Poland.Statistical Analysis STATISTICA 12 and Microsoft Excel were used to analyse the results. The level of significance was p<0.05. The normality of the distribution was tested with the Shapiro–Wilk test. The relationships between the variables were assessed with the χ2 test. Due to the lack of “normality” of the REBA risk distribution, the Mann–Whitney test was used to verify the hypotheses.Results Overall, 48.5% of the examined showed a neck flexion >20, torsion of 80.1%, and 37.5% declared the presence of both types of loads. Also, 14.3% of the examined kept a vertical position, 53.7% flexion to the torso up to 20degrees, 31.4% to 60degrees, and 2.1% to >60degrees. Further, 78.3% of people indicated that they twist the torso. Then, 7% marked the low load's arms position, 45.6% marked the range from 20 to 45degrees, and 39.7% marked the range from 45 to 90degrees. Over 55% showed additional load related to the raising or abduction of the shoulders. Overall, 43% showed a wrong position of forearms. Also, 62.9% showed wrists flexed <15° and the rest showed >15degrees. Again, 79% showed additional twisting and flexion of the wrists. Almost 75% of the examined are exposed to overloads associated with the static load. The examined are not exposed to excessive loads resulting from sudden exertion. REBA scores indicate that the negligible MSDs risk concerns 0.7% examined; low risk, 5.5%; medium risk, 33,1%; high risk, 49.3%; and very high risk, 11.4%. The correlation coeffcients analysis showed that exposure risk is strongly correlated with the overloads on the tested parts of the body in both groups.Conclusion The levels of MSDs risk indicate that hygienists more often should be subjected to periodic check-ups in the workplace. They also need ergonomic interventions (education, preventive technique, physical activity, and improvement of the working environment) and modifications of hygienist's college programs in the field of work ergonomics can be also considered.
Keywords: body position; dental hygienist; musculoskeletal disorder risk; overloads; static load